Trade openness and income inequality in selected developing countries - Tee, Heng Guan; Kaliappan, Shivee Ranjanee; Lee, Chin; Said, Rusmawati (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
The purpose of this paper is to examine the nexus between trade openness and income inequality in the case of eight selected developing countries from 1985 to 2014 under Kuznet framework. Based on the idea of Kuznet curve, income inequality rise with national income growth initially and drop after reaching certain turning point. Most of the papers merely focus on the changing sign that indicated the existence of Kuznet curve. However, they ignored the threshold value whereby the turning point occurred. This paper not only fills the gap by considering the threshold value but also following the idea of “Openness Kuznet Curve” which is another version of Kuznet curve that hardly received attention in empirical studies. This paper follows measurement proposed by Squalli and Wilson (2011) by considering a multidimensional index which is composite trade shares to measure for trade openness. This index not only accounts for the contribution of international trade in terms of GDP but also on the relative size of the country’s international trade compared to the world economy. By considering two dimensions of international trade, the composite trade shares are therefore able to capture the real contributions of trade openness more precisely compared to the widely used trade shares that only account for the share of international trade in GDP alone. Different from most of the empirical study, this paper has found the non-existence of “Openness Kuznet Curve” since the null hypothesis of no threshold effect failed to be rejected at 95 % confidence level. Hence, the linear model is applied and the results from static panel indicated the relationships between trade openness and income inequality were significantly positive when using both composite trade shares and trade shares under the random effect model. This is against with the prediction of Heckscher-Ohlin and Stopler-Samuelson theorem that trade openness is beneficial in reducing income inequality in the case of developing countries. This paper has also proven that it is important to take into account of the multidimensional nature of trade openness since the magnitude of trade openness is found to be relatively smaller than when using the trade shares for measuring trade openness in static panel estimations. By using a relatively more reliable indicator for trade openness, the composite trade shares has able to avoid the overestimation of trade openness on income inequality as indicated by trade shares which ignored the interaction with world dimension of trade openness. Given the evidence of the significantly positive relationships between trade openness and income inequality, the policy makers should anticipate the potential adverse effect that might occur with greater trade openness to ensure greater trade openness continue to be beneficial for the countries.